Atomic-level molybdenum oxide nanorings with full-spectrum absorption and photoresponsive properties. Issue 1 (December 2017) - Yang, Yong; Yang, Yang; Chen, Shuangming; Lu, Qichen; Song, Li; Wei, Yen; Wang, Xun
Abstract Superthin nanostructures, particularly with atomic-level thicknesses, typically display unique optical properties because of their exceptional light–matter interactions. Here, we report a facile strategy for the synthesis of sulfur-doped molybdenum oxide nanorings with an atomic-level size (thickness of 0.5 nm) and a tunable ring-in-ring architecture. These atomic-level nanorings displayed strong photo-absorption in both the visible and infrared-light ranges and acted as a photothermal agent. Under irradiation with an 808 nm laser with an intensity of 1 W/cm2, a composite of the nanorings embedded in polydimethylsiloxane showed an ultrafast photothermal effect, delivering a local temperature of up to 400 °C within 20 s, which to the best of our knowledge is the highest temperature by light irradiation reported to date. Meanwhile, the resulting nanorings were also employed as a photoinitiator to remotely induce a visible-light shape memory response, self-healing, reshaping performance and reversible actuation of dynamic three-dimensional structures. This study demonstrates an advancement towards controlling atomic-level-sized nanostructures and achieving greatly enhanced optical performances for optoelectronics. Nanostructures with atomic-level thicknesses have the potential to exhibit unique size-dependent properties. Here the authors fabricate sulfur-doped molybdenum oxide architectures with tunable ring-in-ring morphologies and strong visible- and IR-light absorption, endowing them with a range of photoresponsive properties.